2014
DOI: 10.1074/jbc.m114.590646
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Receptors for Ion Transport Peptide (ITP) and ITP-like (ITPL) in the Silkworm Bombyx mori

Abstract: Background: Ion transport peptide (ITP) and ITP-like (ITPL) are crustacean hyperglycemic hormone family peptides in insects. Results: Receptors for ITP and ITPL were screened from orphan Bombyx neuropeptide G protein-coupled receptors (BNGRs). Conclusion: BNGR-A2 and -A34 act as ITP receptors, whereas BNGR-A24 functions as an ITPL receptor. Significance: Receptor identifications provide further understandings of biological events by this neuropeptide superfamily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 47 publications
1
73
0
Order By: Relevance
“…It is probably not a coincidence that the tissues which express CHHBP in Eriocheir sinensis are the same as the main target tissues of CHH. Furthermore, in Bombyx mori, expression of the putative ITP receptors BNGR-A2 and BNGR-A34 was restricted to some, but not all of these tissues (Nagai et al, 2014), which is somewhat comparable to the expression profile of CHHBP.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…It is probably not a coincidence that the tissues which express CHHBP in Eriocheir sinensis are the same as the main target tissues of CHH. Furthermore, in Bombyx mori, expression of the putative ITP receptors BNGR-A2 and BNGR-A34 was restricted to some, but not all of these tissues (Nagai et al, 2014), which is somewhat comparable to the expression profile of CHHBP.…”
Section: Discussionmentioning
confidence: 65%
“…These findings provide evidence that CHH is involved in glycogen metabolism in the hepatopancreas. Recently, Nagai and colleagues found that the Bombyx mori orphan neuropeptide G-protein-coupled receptors BNGR-A2 and BNGR-A34 act as ion transport peptide (ITP) receptors and show that BNGR-A24 is an ITP-like (ITPL) receptor (Nagai et al, 2014). However, in crustaceans, the CHH receptor in the hepatopancreas and downstream signal pathway that mediate these processes remain unidentified (Chung et al, 2010;Webster et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…melanogaster corazonin receptor, isoform A ( AAF49928 [ 72 ]); CCAPR, D . melanogaster crustacean cardioactive peptide receptor ( AAF56536 [ 72 ]); CHHR, Bombyx mori neuropeptide receptor A2 ( BAG68400 [ 76 , 77 ]); DH31R, D . melanogaster diuretic hormone 31 receptor, isoform A ( AAN16138 [ 72 ]); DH44R, D .…”
Section: Resultsmentioning
confidence: 99%
“…Pyrokinin receptor Pyrokinin and ITP [189,190] Bombyx Tachykinin receptor TK and ITPL [189,191] Drosophila PK-1 receptor Capa-PK (PK-1) and limostatin [192]…”
Section: Bombyxmentioning
confidence: 99%